Some wood parameters in bulls administered vitamin c at different environmental temperatures - Tufan Keçeci; Ercan Keskin (Eurasian Journal of Veterinary Sciences)
A total of 84 healthy Swiss Brown bulls used in the study in order to investigate the effect of different environmental temperatures and vitamin C administration on the levels of certain blood metabolites. For this purpose the amount of 50 ml/week vitamin C solution contained 20% ascorbic acid (n:7) and the same amount of sterile physiological saline (n;7) were intramuscularly injected within 4 weeks to the bulls which were at the same conditions of maintenance and nutrition at two months intervals during one year. At the same period, the blood samples were taken and the data of environmental temperatures were recorded In hot environmental temperatures (20,8 C; 39.3% relative humidity (RH) and 23.7C; 20.0% RH) serum glucose and total cholesterol levels of the bulls administered vitamin C or sterile physiological saline were determined to be lower levels, when compared to the same values in cold environmental temperatures (3,2ºC: 63.3% BH and 5.3ºC; 77% RH). Although aspartate aminotransferase (AST) activity ol the animals in both groups at hot environmental temperatures was found to be higher amounts than the value at cold environmental temperatures. Vitamin C was not significantly influenced any investigated blood metabolites. Moreover, it was not determined any effect of the environmental temperatures on the serum alkaline phosphatase, urea-nitrogen, total protein, albumin, calcium and inorganic phosphorus levels of the bulls. Consequently, it was determined that the environmental temperatures caused to alter the values of the serum glucose, total cholesterol and AST in Swiss Brown cattle and vitamin C was not influenced on the investigated parameters at the ambient temperatures recorded this experiment.